2010
DOI: 10.1242/dev.048231
|View full text |Cite
|
Sign up to set email alerts
|

The role ofDrosophilaLamin C in muscle function and gene expression

Abstract: SUMMARYThe inner side of the nuclear envelope (NE) is lined with lamins, a meshwork of intermediate filaments that provides structural support for the nucleus and plays roles in many nuclear processes. Lamins, classified as A-or B-types on the basis of biochemical properties, have a conserved globular head, central rod and C-terminal domain that includes an Ig-fold structural motif. In humans, mutations in A-type lamins give rise to diseases that exhibit tissue-specific defects, such as Emery-Dreifuss muscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 113 publications
4
103
1
Order By: Relevance
“…Drosophila has been a useful model for the study of muscular dystrophy, as mutations in homologs of several human disease genes also cause dystrophic phenotypes in flies (Plantié et al, 2015). For example, mutations in dystrophin (Duchenne muscular dystrophy), sarcoglycan gamma and/or delta (limb girdle muscular dystrophy), protein O-mannosyltransferase 1/2 (Walker-Wardburg Syndrome), and lamin A/C (Emery-Dreifuss muscular dystrophy) all show this property (Allikian et al, 2007;Dialynas et al, 2010;Haines et al, 2007;Shcherbata et al, 2007). Wb is the homolog of human laminin subunit alpha 2 (Martin et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila has been a useful model for the study of muscular dystrophy, as mutations in homologs of several human disease genes also cause dystrophic phenotypes in flies (Plantié et al, 2015). For example, mutations in dystrophin (Duchenne muscular dystrophy), sarcoglycan gamma and/or delta (limb girdle muscular dystrophy), protein O-mannosyltransferase 1/2 (Walker-Wardburg Syndrome), and lamin A/C (Emery-Dreifuss muscular dystrophy) all show this property (Allikian et al, 2007;Dialynas et al, 2010;Haines et al, 2007;Shcherbata et al, 2007). Wb is the homolog of human laminin subunit alpha 2 (Martin et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A series of previous studies showed that different nuclear compartments were associated with different genome transactions. For example, genes close to the nuclear periphery nuclear lamina domain were associated with marked transcriptional repression [89][90][91][92]. The positioning of a gene can even be correlated with specific replication timing [93,94].…”
Section: Nuclear Compartments Might Influence the Choice Of Dna Repaimentioning
confidence: 99%
“…One of the mechanisms governing genome organization is the association with nuclear compartments 7 , which participates in the regulation of DNA metabolism. For example, artificial tethering of certain genes to the nuclear lamina can lead to transcriptional repression [8][9][10][11] and gene positioning can be correlated to replication timing 12 . Additionally, components of the transcription machinery have a non-homogeneous distribution in the nucleoplasm 13,14 , suggesting that genes should have the potential to move towards or away from this transcription machinery to be regulated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%